2018
DOI: 10.1167/iovs.18-24258
|View full text |Cite
|
Sign up to set email alerts
|

YAP/TAZ Are Essential for TGF-β2–Mediated Conjunctival Fibrosis

Abstract: PURPOSE. To investigate the roles of Yes-associated protein (YAP)/transcriptional co-activator with PDZ-binding motif (TAZ), the major effector molecules of the Hippo pathway, in TGFb2-mediated conjunctival fibrosis.METHODS. Primary human conjunctival fibroblasts were treated with TGF-b2. The expression of YAP/TAZ was examined by Western blot analyses and immunocytochemistry. The expression of fibrotic proteins and genes were evaluated by Western blot analyses and quantitative real-time PCR, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 61 publications
8
53
0
Order By: Relevance
“…A common mediator of profibrotic responses is the transcriptional comodulators YAP and TAZ . In that YAP/TAZ has been shown to regulate metabolic activity as well as many aspects of the fibroblast response to TGFβ, we next addressed whether YAP/TAZ might be a mediator of PD‐L1 expression downstream of TGFβ signaling. YAP/TAZ levels were decreased using siRNA and PD‐L1 expression was assessed after TGFβ treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common mediator of profibrotic responses is the transcriptional comodulators YAP and TAZ . In that YAP/TAZ has been shown to regulate metabolic activity as well as many aspects of the fibroblast response to TGFβ, we next addressed whether YAP/TAZ might be a mediator of PD‐L1 expression downstream of TGFβ signaling. YAP/TAZ levels were decreased using siRNA and PD‐L1 expression was assessed after TGFβ treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A common mediator of profibrotic responses is the transcriptional comodulators YAP and TAZ. 42 In that YAP/TAZ has been shown to regulate metabolic activity 43 as well as many aspects of the fibroblast response to TGFβ, [44][45][46] we next addressed whether YAP/TAZ might be a mediator of PD-L1 1) and murine (AKR-2B and Swiss 3T3) fibroblast cell lines were stimulated with 5 ng/mL TGFβ (+) or Vehicle (−; 4 Mm HCl + 0.1% BSA) for 18 hours and Western blotted for PD-L1 or GAPDH. B, (Top) MRC5 and AKR-2B cells were stimulated with Vehicle (−) or TGFβ (+) and assessed for PD-L1, collagen 1 (COL1α1), and pSmad3 protein at the indicated times.…”
Section: Yap/taz Regulates Pd-l1 Expression By Tgfβmentioning
confidence: 99%
“…Being potentially relevant to fibrosis, activated YAP/TAZ proteins are translocated to the nucleus where they crosstalk with the TGFβ pathway on a transcriptional level by binding to Smad2/3/4 complexes, as initially discovered in human and mouse embryonic stem cells, mammary epithelial cells, malignant mesothelioma and breast cancer cell lines [14][15][16][17]. It was shown that YAP/TAZ knockdown blocks the profibrotic effects of TGFβ1 [18,19] and TGFβ2 [20] and that substrate stiffness, which impacts YAP/TAZ localization and activity also regulates the output of the TGFβ1 pathway [21].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of YAP, TAZ, CYGF, and CYR61 was decreased when LATS2 was overexpressed, which was consistent with the aforementioned research. CCN family proteins including CYR61 and CTGF, which depend on both YAP and TAZ, 35 have been identified to play important roles in skeletal growth, wound cure, fibrosis, and cancer. 36 Wang et al 37 identified the crucial roles of YAP and TAZ in the regulation of vascular homeostasis.…”
Section: Yap/taz Figurementioning
confidence: 99%